MOTIVASI INDIA MENOLAK PENGHAPUSAN SUBSIDI PANGAN DOMESTIK DALAM KONFERENSI TINGKAT MENTERI WTO IX DI BALI - Silaban, Tulus Fredy; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes about the motivation of India rejecting the elimination of domestic food subsidies in ninth WTO Ministerial Conference at Bali in 2013. This problem occurs when the developed countries that are members of WTO urge the elimination of domestic food subsidies at Ministerial Conference as set out in the Agreement on Agriculture (AOA) in 1995, which aims to reduce the role of government in agriculture and trade to reduce trade barriers on international trade.The writer collects data from books, encyclopedia, journals, mass media and websites to analyze the motivation of India rejecting the elimination of domestic food subsidies in ninth WTO Ministerial Conference at Bali in 2013. The theories applied in this research are foreign policy theory model the decision-making from Richard Snyder and national interest from Donald E. Nuechterlein.The research shows that the motivation of India rejecting the elimination of domestic food subsidies in WTO Ministerial Conference because the India goverment considers the elimination of domestic food subsidies would adversely affect the condition of agriculture in India. While at the same time the Indian goverment is trying to achieve self-sufficiency of food in India with sufficient national food stocks.Keywords : Subsidies, Food, Motivation